(untitled) - Zastrow, Charles (Boston, MA, 2017)
The twelfth edition includes comprehensive Council on Social Work Education (CSWE) core content that aligns with the latest Educational Policy and Accreditation Standards (EPAS), as well as insightful coverage of new and emerging issues, making it the number one book for social work students.
Công tác xã hội,Thực hành công tác xã hội
Keywords: Trung tâm Học liệu ĐHCT,Phúc lợi công cộng,Public welfare,Dịch vụ xã hội,Social service; Hoa Kỳ,United States.,Hoa Kỳ,United States